The impact of the COVID-19 pandemic on the diet, training habits and fitness of masters cyclists - Shaw, K. A.; Bertrand, L.; Deprez, D.; Ko, J.; Zello, G. A.; Chilibeck, P. D. (Nutrition and Health, 2021)
Background: The number of Masters-level athletes (= 35 years of age) taking part in cycling has increased in the past years which may have beneficial effects on their health. The restrictions brought on by the COVID-19 pandemic has the potential to negatively impact the diet, training and fitness of these individuals due to restrictions in place to slow the spread of the virus. Aim: To investigate how the COVID-19 pandemic impacted the diet, training and fitness of Masters-level cyclists. Methods: 32 Masters cyclists (12 males, 20 females; mean age 47 ± 10 years) completed two incremental exercise tests one month apart during the pandemic to assess sport-specific fitness. Participants also completed online questionnaires to report their sedentary behavior and dietary intake before and during the pandemic, and their training volume and intensity for a specified week in February (before the pandemic) and each of March, April and May (during the pandemic). Results: No differences were seen in fitness (p = 0.6), training volume (p = 0.24) or intensity (p = 0.79) and sedentary behavior (p = 0.14) during the pandemic. Energy intake was unchanged (p = 1.0) during the pandemic, but participants consumed lower amounts of key nutrients such as fiber, vitamin A, omega-3 fatty acids and potassium (p < 0.05) while consuming more alcohol (p = 0.008) and vitamin C (p = 0.03). Conclusions: Our data shows that the COVID-19 pandemic has undesirable effects on nutrient and alcohol intake of Masters cyclists without impacting their training regimes, which may have adverse effects on their overall health and fitness in the long term.